Application of empirical methods to estimate crown pillar failure in caving mines - Jarufe, J (Caving 2022: Proceedings of the Fifth International Conference on Block and Sublevel Caving, 2022)
Crown pillar in cave mines corresponds to the solid rock pillar located between the cave and the surface in the early stages of the caving process. A correct estimation of the failure time may provide valuable assistance in planning underground and surface activities. While modelling has shown important advances in the simulation of the breakthrough process, empirical tools may provide an early warning of the pillar failure process, delivering early guidelines about when to isolate surface infrastructure or change draw velocities due to the change in the mined column height. This paper reviews empirical methods to estimate crown pillar stability and their application in the breakthrough process in block cave mines, evidenced by a case study in Chuquicamata underground mine.
Keywords: caving